THE PARADOX BEHIND THE EXISTENCE OF GAY CONVERSION THERAPY AS DEPICTED IN GARRARD CONLEY’S MEMOIR BOY ERASED - Sekar Yolanda Azza (Rubikon : Journal of Transnational American Studies, 2020)
The issues of minorities still become an interesting topic to be discussed since practically the laws sometimes cannot protect the rights of the minorities. Homosexuals are one of the minority groups in the United States struggling with homophobia. The existence of gay conversion therapy is a paradox in the multicultural country. This research is conducted to examine how the portrayal of homophobia in gay conversion therapy and how the paradox of multiculturalism depicted in Conley’s memoir entitled Boy Erased. The primary data of this research are the dialog and narration in the memoirpublished in 2016,which contains the irony behind the existence of gay conversion therapy. The secondary data are taken from articles and current news that relates to the issues. The post-nationalism approach, homophobia theory, and multiculturalism theory are used to analyze the data. The study found institutionalized homophobia at Love in Action (LIA) as the gay conversion therapy institution. The reasons behind the existence of gay conversion therapy are the paradox of toleration, lack of equal recognition, and the inability to provide positive accommodation for homosexuals. The existence of gay conversion therapy proved that the struggles of homosexuals in the United States still need to be overcome.